Efeito da triancinolona na apoptose celular e nas alterações morfológicas em queloides - João Marcio Prazeres dos Santos (2014)
Introduction: Scar is the end product of ordinated events for the tissues repair; however it may be unsatisfactory and can generate deformities like keloids. In perspective of the incomplete elucidation of keloid´s etiology, as well as the involvement of apoptosis in this genesis, they are poorly treated with variable rates of success, as seen with injectable corticosteroids. Objective: To compare the effect of injectable triamcinolone in keloid scars on the number of cells undergoing apoptosis and to evaluate the effect of injectable Triamcinolone in change the length, height and thickness. Methods: This study consists in a prospective, controlled, randomized, single-masked clinical trial, conducted with fifteen patients with ear keloids divided into two groups: group 1 - seven patients underwent excisions of keloids and group 2 - eight patients underwent excisions of lesions after three sessions of infiltration with one mL of Triamcinolone acetonide (20mg/mL) with three week intervals between them and between the last session and surgery. The two groups were homogeneous regarding age, gender and evolution of keloid scar. The keloid scars of patients in group 2 were measured for the length, height and thickness before injection of triamcinolone and before surgery, using a Rhosse® caliper rule. The specimens were stained with hematoxylin-eosin for morphologic detailing and manually cell quantification by a masked observer. The apoptotic index was defined by the ratio of number of apoptotic cells by total cell number, multiplied by one hundred. To quantifying the apoptotic index we considered apoptotic cells if they presented at least three characteristics as anoiquia, cytoplasmatic condensation, nuclear condensation, nuclear fragmentation and cell fragmentation. Results: The apoptotic index in group 1 was 56.82 and 68.55 in group 2, showing no significant difference in apoptosis (p = 0.0971). There was reduction in the size of triamcinolone infiltrated keloids, but it was not significative. The reduction was 10.12% on the length (p = 0.,6598), 11.94% on the height (p = 0.4981) and 15.62% on the thickness (p = 0.4027). Conclusion: This study, in its conditions, concluded that the infiltration of triamcinolone in keloid scars has not increased the number of apoptosis and has not reduced the size, length, height and thickness of keloid.